Peningkatan Aktivitas dan Hasil Belajar Ilmu Pengetahuan Alam Menggunakan Pendekatan Inkuiri - Sri Zulyani (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2017)
In this case focus to increase activity and IPA student learning outcomes through inquiry learning approach. Type of study is a descriptive qualitative research methods class action. The results obtained in this study show that: 1) Average activity in cycle I (48.73%) increased by 14.92% in cycle II (63.65%), 2) Improved student learning outcomes of the cycle I to the second cycle of 28.57% from 57.14% to 85.71% cycle I to cycle II on the subject of IPA. Based on these results, the suggestions can be submitted are: to improve the quality of teachers should be teaching mathematic in the inquiry learning approach. For researchers, in order to do further research on the effectiveness of learning by using the inquiry approach related to learning outcomes and learning processes, and are expected to contribute to the awakening of science and technology, especially learning IPA.